Peran Green accounting dalam Meningkatkan Kualitas Sustainability Report - Maharani, Shavira Aisyah; Akbar, Fajar Syaiful (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Tujuan: This study aims to examine the effect of green accounting on the quality of sustainability reports among publicly listed companies in Indonesia during the 2021–2023 period. Green accounting is measured using three indicators: environmental operational costs, research and development (R&D) costs, and recycling costs. Desain Penelitian dan Metodologi: A quantitative approach was employed, utilizing secondary data collected from the annual reports and sustainability reports of 43 purposively selected companies listed on the Indonesia Stock Exchange (IDX). The study employs simple linear regression analysis to assess the partial effect of green accounting on the quality of sustainability reports. Hasil dan Pembahasan: The findings indicate that green accounting has a positive and significant influence on the quality of sustainability reports. These results highlight the strategic role of green accounting in enhancing corporate accountability and environmental disclosure practices. The study supports the relevance of integrating environmental costs into financial reporting as part of sustainable business practices. Implikasi: Future research is encouraged to explore other influencing factors such as stakeholder pressure or corporate governance, as well as to extend the scope across different sectors and countries for broader generalization.